Pulmonary perfusion in long-term survivors of COVID-19-related severe acute respiratory distress syndrome treated by extracorporeal membrane oxygenation - Miksová, Lucie; Dytrych, Vladimír; Ptáčník, Václav; Balík, Martin; Linhart, Aleš; Bělohlávek, Jan; Jansa, Pavel (Pulmonary circulation, 2024)
COVID-19 associates with a hypercoagulant state and an increased risk for venous thromboembolic events (VTEs). Whether severe COVID-19 infection requiring extracorporeal membrane oxygenation (ECMO) support might lead to chronic pulmonary perfusion abnormalities and chronic thromboembolic pulmonary disease/hypertension remains unclear. The purpose of this study was to evaluate chronic pulmonary perfusion abnormalities in long-term survivors of COVID-19-related severe acute respiratory distress syndrome (ARDS) treated by ECMO at our institution. Pulmonary perfusion was examined by ventilation/perfusion (V/Q) single-photon emission computed tomography or V/Q planar scintigraphy at least 3 months after ECMO explantation, comorbidities and incidence of thromboembolic events were recorded as well. Of 172 COVID-19 patients treated by ECMO for severe COVID-19 pneumonia between March 2020 and November 2021, only 80 were successfully weaned from ECMO. Of those, 37 patients were enrolled into the present analysis (27% female, mean age 52 years). Median duration of ECMO support was 12 days. In 24 (65%) patients VTE was recorded in the acute phase (23 patients developed ECMO cannula-related deep vein thrombosis, 5 of them had also a pulmonary embolism, and one thrombus was associated with a central catheter). The median duration between ECMO explantation and assessment of pulmonary perfusion was 420 days. No segmental or larger mismatched perfusion defects were then detected in any patient. In conclusion, in long-term survivors of COVID-19-related ARDS treated by ECMO, no persistent pulmonary perfusion abnormalities were detected although VTE was common.